Toxicidade e potencial antitumoral de um derivado sintético 2-aminotiofeno - Moura, Ana Paula Gomes (2017)
The 2 - [(1H-indol-3-yl-methylidene) -amino] -5,6,7,8-tetrahydro-4H-cyclohepta [b] thiophene-3-carbonitrile (SB-44) is a derived from 2-amino-thiophene ring that has reports of anti-leishmania and antitumor activities. However, there is no literature data related to its mechanisms of antitumor action. Therefore, this work aimed to evaluate the toxicity and antitumor activity of SB-44 in Ehrlich ascites carcinoma model, as well as, to investigate possible mechanisms of action involved in this effect. Initially, the SB-44 acute not clinical toxicity was evaluated in mice per intraperitoneal route (i.p.). SB-44 (2000 mg/kg) did not induced death. Still, in the pharmacological behavioral screening the only effect induced by SB-44 was ptosis, that disappeared after 4 hours of treatment. The DL50 (50% lethal dose) was estimated as higher than 5000mg/kg, considering the guide n. 423 from Organization for Economic Co-operation and Development (OECD), what indicates acute toxicity lower of the substance. For the genotoxicity evaluation the test of micronuclei was performed, being observed that SB-44 (2000 mg/kg, i.p.) did not induced increase in the numbers of micronuclei erythrocytes, suggesting low genotoxicity. In a model of Ehrlich's Ascitic Carcinoma, was observed that SB-44 (100 mg/kg, i.p.) reduced the forma dose dependente o parameters cell viability (p<0.05). The evaluation of the antitumor action mechanism began with the cell cycle analysis. It was observed that SB-44 (100 mg/kg) induced the appearance of the sub G1 peak (p<0.001), what is suggestive of apoptosis. It was determined the vessels microdensity in the peritoneum, being observed a reduction of this parameter (p<0.001) after the treatment with SB-44 (100 mg/kg). In relation to the influence of SB-44 (100 mg/kg) in inflammatory mediators of tumor microenvironment, it can be observed the reduction of cytocines IL-10 e IFN-γ (p<0.05), what indicates modulation of the immune fighting against the tumor. Considering the wide role the oxidative stress in the propagation of tumors, it was evaluated the effect of SB-44 by the fluorometric assay of 2-70-dichlorofluorescein diacetate (DCFH-DA). It was observed reduction on oxidative stress after the treatment with SB-44 (100 mg/kg) (p<0.05), what suggests antioxidant effects. Still, it was detected that SB-44 (100 mg/kg) promoted reduction of the nitrict oxide (NO) (p<0.05), a key mediator involved in growth processes, angiogenesis and tumor metastasis. Among all toxicity parameters evaluated (metabolic parameters, biochemical, hematological and histological), it was observed that SB-44 (100 mg/kg) induced only hepatotoxicity, characterized by esteatosis and apoptosis in the hepatic tissue. Whole data shown suggests that SB-44 has antitumor activity by interfering in the cell cycle progression and to exert immunomodulators effects, besides presenting antioxidant activity and reduction of NO levels, what, possibly, is related to its antiangiogenic effect